Effect of Mangifera Indica Root Methanolic Extract on Streptozotocin Induced Diabetic Albino Rats - Umaru, Kerenhappuch Isaac; Tansaba, Akafa Andes; Nanmar, Chakfa; Umaru, Isaac John; Ugoeze, Egeonu Stephen (Darul Yasin Al Sys, 2024)
The growing prevalence of diabetes in both developed and developing nations has prompted scientists to intensify their research efforts in identifying potent therapeutic compounds from natural sources. These compounds are aimed at more effectively treating and managing diabetes. The aim of this research is to determine the potentials of Mangifera Indica on induced hyperglycemic rats. The materials and methods : The roots will be cut into small pieces, air-dried and 100g of the root powdered soaked , extracted in rotary evaporator, fort albino rats is used. Diabetes will be induced in rats by injecting them intraperitoneally (i.p.) with freshly prepared streptozotocin (STZ) dissolved in citrate buffer (0.1 M pH 4.5) after an overnight fast and Hyperglycemia confirmed. Thirty albino rats is randomly divided into six groups, each consisting of five rats: group 1-6. Group 1-3 control groups, NC (Normal non-treated control), DM (Negative control rats), PC (Positive Control) group 4-6 (Mangifera indica treated diabetic rats). The NC and DM (control groups) will be given distilled water, while the MI and DM + MI (experimental groups) will receive Mangifera indica extract at a dose of 100, 200 and 400 mg/kg/b.wt. Results: Day one blood glucose levels was lowered significantly (p < 0.05). Day three treatments with standard drug and 100 mg/kg body weight extract lowered blood glucose significantly (p < 0.05) close to normal after induction with alloxan. The results of selected liver test indicates that AST decreased significantly, ALT increased significantly, ALP increased significantly, TP decreased significantly, GLB decreased significantly, TB increased significantly, DB increased significantly, INDB increased significantly. The results of kidney function test show that urea increased significantly, no significant difference shown in creatinine, potassium level were raised significantly, chloride and carbon dioxide were elevated significantly.